Pengembangan Video Pembelajaran Berbasis AI "LARAS" dalam Surah Al-Kausar pada Pembelajaran PAI Kelas 2 SD - Aeni, Ani Nur; Hermawan, Dery Aditya; Aiska, Feymi Fa'adillah; Ulfana, Karisma Tita (AS-SABIQUN, 2024)
The purpose of this study was to determine the degree to which the use of animated videos in educational materials improves student comprehension of the subject matter and has a positive influence on the learning process. The Design and Development (D&D) ADDIE paradigm, which has five stages—analysis, design, development, implementation, and evaluation—was the methodology employed in this study. Additionally, this study employs a qualitative approach method that involves distributing questionnaires and conducting interviews in Malangbong's class II primary schools. The study's findings indicate that media professionals and subject matter experts alike think highly of this animated video-based learning resource, placing it in the extremely suitable category. Additionally, it aims to elicit positive feedback from students in order to boost their enthusiasm in learning Surah Al-Kausar content for PAI courses. We may infer that the influence of this animated video-based learning medium on students' comprehension of Surah Al-Kausar is positive and enhances their learning experience.